Multi-Hazards and Existing Data: A Transboundary Assessment for Climate Planning - Alessandra Longo; Chiara Semenzin; Linda Zardo (Land)
Many regions worldwide are exposed to multiple omnipresent hazards occurring in complex interactions. However, multi-hazard assessments are not yet fully integrated into current planning tools, particularly when referring to transboundary areas. This work aims to enable spatial planners to include multi-hazard assessments in their climate change adaptation measures using available data. We focus on a set of hazards (e.g., extreme heat, drought, landslide) and propose a four-step methodology to (i) harmonise existing data from different databases and scales for multi-hazard assessment and mapping and (ii) to read identified multi-hazard bundles in homogeneous territorial areas. The methodology, whose outputs are replicable in other EU contexts, is applied to the illustrative case of Northeast Italy. The results show a significant difference between hazards with a ‘dichotomous’ spatial behaviour (shocks) and those with a more complex and nuanced one (stresses). The harmonised maps for the single hazards represent a new piece of knowledge for our territory since, to date, there are no comparable maps with this level of definition to understand hazards’ spatial distribution and interactions between transboundary areas. This study does present some limitations, including putting together data with a remarkable difference in definition for some hazards.